THE IMPORTANCE OF DIGITALIZATION IN THE ECONOMY OF UZBEKISTAN - Xusanboyeva Tursunoy; Egamberdiyev Shavkatbek (Galaxy International Interdisciplinary Research Journal, 2024)
This article provides information on the impact of digitization and the digital economy on the economy of Uzbekistan. Information about state programs and presidential decisions, laws on the digital economy is presented. The practical results of these legislation are also given.